Dietary arginine supplementation in multiparous sows during lactation improves the weight gain of suckling piglets - Cui ZHU; Chang-yi GUO; Kai-guo GAO; Li WANG; Zhuang CHEN; Xian-yong MA; Zong-yong JIANG (Journal of Integrative Agriculture, 2017)
This study investigated the effects of dietary arginine (Arg) supplementation, just during lactation, on sow and litter performance, plasma concentrations of metabolites and hormones, and milk yield and composition in multiparous sows. Thirty-one sows were randomly assigned to 3 dietary treatments supplemented with 0.0 (control, n=10), 0.5% (n=10), or 1.0% (n=11) L-Arg-HCI, respectively. Experimental diets were provided to the sows from d 3 to 21 of lactation. Plasma and milk samples were collected at d 14 and 21 of lactation. The average daily gain (ADG) of piglets from sows fed diets supplemented with 0.5 or 1.0% L-Arg-HCI at d 3 to 14 of lactation, were higher than that of controls (P<0.05). Maternal supplementation with 1.0% L-Arg-HCI also increased ADG of piglets between d 3 and 21 of lactation than that of the controls (P<0.05). There was no significant effect of supplementation on average daily feed intake (ADFI), body weight loss, and backfat thickness loss of lactating sows. Supplementation with 0.5 or 1.0% L-Arg-HCI had a trend towards increasing milk yields and milk fat contents (0.05<P<0.10); milk protein and lactose were unchanged. Supplementation with 1.0% L-Arg-HCI increased plasma concentrations of prolactin and insulin in sows at d 14 and 21 of lactation, and plasma concentrations of non-esterified fatty acid (NEFA), insulin-like growth factor-1 (IGF-1), and nitric oxide (NO) in sows at d 21 of lactation, when compared to the controls (P<0.05). Supplementation with 1.0% L-Arg-HCI increased IGF-1 and spermine in milk at d 14 of lactation, relative to the controls (P<0.05). Plasma Arg concentrations at d 14 and 21 of lactation, as well as plasma NO level and milk IGF-1 at d 21 of lactation, were increased, while plasma urea nitrogen (PUN) concentration at d 14 and 21 of lactation was decreased, by supplementation with 0.5 or 1.0% L-Arg-HCI when compared to the controls (P<0.05). Collectively, dietary supplementation of multiparous sows with Arg, just during lactation, is beneficial for enhancing litter weight gain but the complete mechanism remains to be determined and may involve in the maternal endocrine changes and milk polyamines contents.